2018
DOI: 10.1080/14616734.2018.1469653
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mind-mindedness and its association with attachment: the case of Arab infants and mothers in Israel

Abstract: We examined the association between maternal Mind-Mindedness (MM) and secure attachment in an Arab sample in Israel. Seventy-six infant-mother dyads were observed during free play to assess maternal MM and in the Strange Situation Procedure to assess attachment. Mothers of secure infants were hypothesized to use more appropriate and fewer non-attuned mind-related comments than mothers of insecure infants. The results showed that mothers of secure infants used more appropriate mind-related comments than mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
0
2
Order By: Relevance
“…Past studies reported that appropriate and nonattuned MM had differential associations with sensitivity and mother-infant attachment (e.g., [9,19,27]). Although previous studies have mostly reported lack of associations between the two dimensions of MM [4], in the present study appropriated and nonattuned MM were significantly correlated ( r = .24; see [123] for a similar correlation), perhaps suggesting that some mothers in the sample had a general tendency to use more mental-states words (regardless of their appropriateness). In general, our results suggest that each MM dimension may rely on a different cognitive process, and that each is moderated by a different child-related factor: Appropriate MM was associated with updating and moderated by child temperament, and nonattuned MM was associated with resistance to interference among mothers of full-terms.…”
Section: Discussioncontrasting
confidence: 50%
“…Past studies reported that appropriate and nonattuned MM had differential associations with sensitivity and mother-infant attachment (e.g., [9,19,27]). Although previous studies have mostly reported lack of associations between the two dimensions of MM [4], in the present study appropriated and nonattuned MM were significantly correlated ( r = .24; see [123] for a similar correlation), perhaps suggesting that some mothers in the sample had a general tendency to use more mental-states words (regardless of their appropriateness). In general, our results suggest that each MM dimension may rely on a different cognitive process, and that each is moderated by a different child-related factor: Appropriate MM was associated with updating and moderated by child temperament, and nonattuned MM was associated with resistance to interference among mothers of full-terms.…”
Section: Discussioncontrasting
confidence: 50%
“…Past studies reported that appropriate and nonattuned MM had differential associations with sensitivity and mother-infant attachment (e.g., [9,19,27]). Although previous studies have mostly reported lack of associations between the two dimensions of MM [4], in the present study appropriated and nonattuned MM were significantly correlated (r = .24; see [123] for a similar correlation), perhaps suggesting that some mothers in the sample had a general tendency to use more mentalstates words (regardless of their appropriateness). In general, our results suggest that each MM dimension may rely on a different cognitive process, and that each is moderated by a different child-related factor: Appropriate MM was associated with updating and moderated by child temperament, and nonattuned MM was associated with resistance to interference among mothers of full-terms.…”
Section: The Multidimensionality Of Mind-mindednesscontrasting
confidence: 45%